2011
DOI: 10.1007/s10509-011-0781-z
|View full text |Cite
|
Sign up to set email alerts
|

Early universe cosmology with particle creation: kinematics tests

Abstract: We study some properties of the early evolution of the universe with particle creation in the framework of the flat Friedmann-Robertson-Walker line element. The field equations are solved by using "gamma-law" equation of state p = (γ − 1)ρ, where the parameter γ varies with cosmological time. A unified description of the early evolution of the universe is presented in which an inflationary phase is followed by a radiation-dominated phase. Exact expressions for the lookback time, proper distance, luminosity dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 25 publications
0
9
1
Order By: Relevance
“…The astrophysical phenomena such as look-back time, luminosity distance are also discussed and show that the models are compatible with present observations. It is important to note that when φ → 0, our results resembles to (Singh and Beesham 2011b). Thus, even if we observe an isotropic expansion in the present universe we still cannot rule out possibility of Dark Energy with an anisotropic EoS within the framework of Saez-Ballester theory of gravitation in Homogeneous-Hypersurface space-time.…”
Section: Resultscontrasting
confidence: 52%
See 1 more Smart Citation
“…The astrophysical phenomena such as look-back time, luminosity distance are also discussed and show that the models are compatible with present observations. It is important to note that when φ → 0, our results resembles to (Singh and Beesham 2011b). Thus, even if we observe an isotropic expansion in the present universe we still cannot rule out possibility of Dark Energy with an anisotropic EoS within the framework of Saez-Ballester theory of gravitation in Homogeneous-Hypersurface space-time.…”
Section: Resultscontrasting
confidence: 52%
“…For this model, we have noted that the volume of the universe expands indefinitely for all values of n. The average scale factor has a linear growth with constant velocity and q = 0 as n = 1, which shows the marginal inflation (Singh and Beesham 2011b). At t = 0, the scale factor vanishes and hence the model has an initial point singularity.…”
Section: Resultsmentioning
confidence: 79%
“…[31]), (17) and (19) reduce to (14) and 13of [31]. Further, In the limit α → 0, the above equation reduces to (16) in [11].…”
Section: Model With Matter Creation and Solutionmentioning
confidence: 93%
“…In this context, Many authors [10][11][12][13][14][15][16][17] have discussed Friedmann-Robertson-Walker line element with matter creation cosmology and analyzed the results through the observations. It has been shown that the matter creation models are consistent with the observations.…”
Section: Introductionmentioning
confidence: 99%
“…Singh (1999, 1997) have studied flat FRW model with variable equation of state parameter in BD theory. Recently, Singh and Beesham (2011) have studied the early universe cosmology with particle creation and discussed the kinematics tests of the findings.…”
mentioning
confidence: 99%